Timing of Conditioned Eyeblink Responses Is Impaired in Cerebellar Patients - Gerwig, Marcus (J Neurosci, 2005)
In the present study, timing of conditioned eyeblink responses (CRs) was investigated in cerebellar patients and age-matched controls using a standard delay paradigm. Findings were compared with previously published data of CR incidences in the same patient population (Gerwig et al., 2003; Timmann et al., 2005). Sixteen patients with pure cortical cerebellar degeneration (spinocerebellar ataxia type 6 and idiopathic cerebellar ataxia), 14 patients with lesions within the territory of the superior cerebellar artery, and 13 patients with infarctions within the territory of the posterior inferior cerebellar artery were included. The affected cerebellar lobules and possible involvement of cerebellar nuclei were determined by three-dimensional magnetic resonance imaging (MRI) in patients with focal lesions (n = 27). Based on a voxel-by-voxel analysis, MRI lesion data were related to eyeblink conditioning data. CR incidence was significantly reduced, and CRs occurred significantly earlier in patients with cortical cerebellar degeneration and lesions of the superior cerebellum compared with controls. Incidence and timing of CRs was not impaired in patients with lesions restricted to the posterior and inferior cerebellum. Voxel-based MRI analysis revealed that cortical areas within the anterior lobe (Larsell lobule HV) were most significantly related to timing deficits, whereas reduced CR incidences were related to more caudal parts (lobule HVI) of the superior cerebellar cortex. The present data suggest that different parts of the superior cerebellar cortex may be involved in the formation of the stimulus association and appropriate timing of conditioned eyeblink responses in humans. Extracerebellar premotoneuronal disinhibition, however, is another possible explanation for changes in CR timing.